Validation of the German version of the Asthma Impairment and Risk Questionnaire (AIRQ) - Kanniess, Frank; Defosse, Kerstin; Lommatzsch, Marek; Schultz, Thomas; Timmermann, Hartmut; Schmidt, Olaf; Heindl, Stefan; Baumann, Hans Jörg; Buhl, Roland; Taube, Christian; Höing, Fabian; Korn, Stephanie (Pneumologie, 2024)
Background The Asthma Impairment and Risk Questionnaire (AIRQ), a 10-item, equally weighted, yes/no tool assessing symptom impairment and risk of exacerbations in patients with asthma aged ≥12 years, was developed and validated in a US patient population to evaluate varying levels of asthma control. This study aimed to validate the German language version of the AIRQ in patients aged ≥12 years with different levels of asthma control. Methods A cross-sectional, observational, multi-centre study comprising a single visit was conducted in multiple specialised asthma centres and general practices in Germany. A total of 300 patients completed the following measures: 1) Patient Sociodemographic and Clinical Questionnaire, 2) AIRQ, 3) Asthma Control Test (ACT), and 4) Asthma Control Questionnaire (ACQ-6). Logistic regression analyses were conducted to assess the AIRQ score cut points with the greatest predictive validity in discriminating between different control levels relative to a standard of ACT plus prior-year exacerbations or ACQ-6 plus prior-year exacerbations. Results The German version of the AIRQ demonstrated a robust capability to correctly identify well-controlled versus not well- or very poorly controlled (AUC values of 0.90 or higher) and well- or not well-controlled versus very poorly controlled asthma (AUC values of 0.89 or higher). Conclusions The German version of the AIRQ is a suitable tool to identify adults with varying levels of asthma control, which in turn can help to accurately identify patients with uncontrolled asthma in clinical practice.
Keywords: AIRQ; asthma; questionnaire